Negative impact of insomnia and daytime sleepiness on quality of life in individuals with the cyclin‐dependent kinase‐like 5 deficiency disorder. (12th April 2022) - Downs, Jenny; Jacoby, Peter; Saldaris, Jacinta; Leonard, Helen; Benke, Tim; Marsh, Eric; Demarest, Scott
Summary: Cyclin‐dependent kinase‐like 5 ( CDKL5 ) gene pathogenic variants result in CDKL5 deficiency disorder (CDD). Early onset intractable epilepsy and severe developmental delays are prominent symptoms of CDD. Comorbid sleep disturbances are a major concerning symptom for families. We aimed to explore the relationship between insomnia, daytime sleepiness, sleep medications and quality of life in children with CDD. Caregivers of 129 children with CDD in the International CDKL5 Disorder Database completed the Quality‐of‐Life Inventory‐Disability (QI‐Disability) questionnaire and "Disorders of Maintaining Sleep" (DIMS) and the "Disorders of Excessive Somnolence" (DOES) items of the Sleep Disturbance Scale for Children. Adjusting for covariates, a unit increase in DOES score was associated with reduced quality of life total (coefficient −3.06, 95% confidence interval [CI] 1.35–7.80), physical health (coefficient −7.20, 95% CI −10.64, −3.76) and negative emotions (coefficient −3.90, 95% CI −7.38, −0.42) scores. Adjusting for covariates, a unit increase in DIMS score was associated with reduced negative emotions (coefficient −6.02, 95% CI −10.18, −2.86). Use of sleep medications had small influences on the effect sizes. This study highlights the importance of sleep problems as a determinant of quality of life in children with CDD, consistent with effects observed for other groups of children with intellectual disability. Excessive daytime sleepiness was particularly associated with detrimental effects on quality of life. Further research in optimal behavioural and pharmaceutical management of sleep problems for this population is required.